Isolation of Straight Chain Alcohol and Ester from Sterculia guttata - KATADE, SUSHAMA; DESHMUKH, MADHAVI; PHALGUNE, USHA; BISWAS, SUJATA; DESHPANDE, NIRMALA (Asian Journal of Chemistry, 2010)
A straight chain ester, nonacosanoic acid, methyl ester was isolated for the first time from acetone extract of Sterculia guttata. Saponification of petroleum ether extract of Sterculia gutatta was carried out. Unsaponifiable matter was further purified by repeated column chromatography followed by repeated mixed solvent crystallization to afford docosanol. The structures of both the compounds were confirmed by spectral analysis.